2012
DOI: 10.3402/tellusb.v64i0.17158
|View full text |Cite
|
Sign up to set email alerts
|

A study of new particle formation in the marine boundary layer over the central Arctic Ocean using a flexible multicomponent aerosol dynamic model

Abstract: A B S T R A C T Enhancement of number concentrations of particles with sizes less than 25 nm diameter has been frequently observed in the boundary layer over the central Arctic Ocean during summer. The sectional aerosol dynamics model for Marine Aerosol Formation (MAFOR) was applied to evaluate the capability of different nucleation mechanisms to reproduce nucleation events observed during three expeditions (1996, 2001 and 2008) onboard the Swedish icebreaker Oden. Model calculations suggest that a source ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
82
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(86 citation statements)
references
References 85 publications
(131 reference statements)
4
82
0
Order By: Relevance
“…In hourly data from 2003 to 2010 at the continental reference station Melpitz (Heintzenberg et al, 1998), e.g., a monomodal distribution at the lowest values of N26 (<30 cm −3 ) with a peak at about 110 nm builds up to a broad and much less structured ultrafine region with modes at 42 nm and 17 nm with increasing N26. This is consistent with observations of the concurrent appearance of several distinct particle sizes below 50 nm during typical nucleation events over the pack ice Bigg, 1999, 2010;Karl et al, 2012).…”
Section: Structural Analysis Of the Size Distributions Of The Four Yearssupporting
confidence: 79%
See 3 more Smart Citations
“…In hourly data from 2003 to 2010 at the continental reference station Melpitz (Heintzenberg et al, 1998), e.g., a monomodal distribution at the lowest values of N26 (<30 cm −3 ) with a peak at about 110 nm builds up to a broad and much less structured ultrafine region with modes at 42 nm and 17 nm with increasing N26. This is consistent with observations of the concurrent appearance of several distinct particle sizes below 50 nm during typical nucleation events over the pack ice Bigg, 1999, 2010;Karl et al, 2012).…”
Section: Structural Analysis Of the Size Distributions Of The Four Yearssupporting
confidence: 79%
“…In several analyzed events, observed in 1996, 2001, and 2008, conventional state-of-the-art nucleation mechanisms (Karl et al, 2012) applied in numerical models could not explain the simultaneous number enhancement of particles in the 20-50 nm diameter size range. The analyzed cases covered the central Arctic, the marginal ice zone and open waters.…”
Section: Aerosol Transport Over the Pack Icementioning
confidence: 99%
See 2 more Smart Citations
“…Several field studies have shown enhanced MSA concentrations in small particles when ammonia or amines are present (37,38), supporting a role for MSA and amines in new particle formation. The impact of MSA and amines on new particle formation may be especially important in the remote marine atmosphere, particularly in polar regions (39)(40)(41). However, mechanisms of particle formation in such areas remain unclear.…”
mentioning
confidence: 99%